Webmaster in a nutshell - Spainhour, Stephen (O'Reilly, 1999)
"Webmaster in a Nutshell pulls together in a single volume all the essential reference information for webmasters working on Unix-based web servers." "In this second edition of Webmaster in a Nutshell, we've updated our material to include the latest versions of HTML and Javascript, and also expanded the book to cover the newest technologies emerging on the Web."--Jacket